Cataract‐Causing Mutant R188C of βB2 Crystallin With Low Structural Stability is Sensitive to Environmental Stresses and Prone to Aggregates Formation - Yibo Yu; Silong Chen; Ying Zhang; Hang Song; Jiarui Guo; Chengpeng Wu; Wei Wu; Jingjie Xu; Xiaoyu Cheng; Chenqi Luo; Jing Guo; Yip Chee Chew; et al. (Exploration)
ABSTRACT This study investigated a Chinese family with congenital posterior polar cataracts linked to the βB2‐R188C mutation. βB2‐crystallin, a key structural component of the lens, is crucial for maintaining lens transparency and stability. We examined the effects of the R188C mutation on βB2‐crystallin's structural stability and resistance to environmental stressors using purified proteins and cellular models. The βB2‐R188C mutant showed poor stability and a tendency to aggregate under physiological and pathological conditions. The mutation disrupted the oligomerization equilibrium, causing dissociation of dimers into monomers. Molecular dynamics simulations and spectroscopic experiments revealed abnormal protein folding induced by the R188C mutation, increasing susceptibility to environmental stressors. Aggregation was observed in both prokaryotic and eukaryotic models under normal conditions, with enhanced severity under environmental stressors. Notably, lanosterol treatment or αB‐crystallin partially reversed aggregation. In summary, the R188C mutation promotes abnormal aggregation by destabilizing βB2‐crystallin and disrupting oligomerization equilibrium, potentially leading to cataract formation. Targeting aggregate formation with small molecules like lanosterol or enhancing molecular chaperone activity offers a promising strategy for cataract prevention and treatment.